Development of a DSP-based fuzzy PI controller for an online optimal PWM control scheme for a multilevel inverter - Ahmad Azli, Naziha; Wong, S. N. (2005)
Previous work has presented the incorporation of a non conventional inverter topology known as multilevel inverter with an optimal PWM based control scheme for high voltage AC power supply applications. A Fuzzy Proportional Integral Controller (FPIC) takes a role in the control scheme in providing stronger control action for a large voltage error and a smoother control action for a small voltage error in the multilevel inverter output. This in turn ensures that high quality output voltage at a fixed frequency is always maintained on the inverter output while the transient response improved regardless of the loading conditions. This paper focuses mainly on the FPIC and its implementation using a digital signal processor (DSP) as part of the hardware implementation of the control scheme. A test conducted on the DSP-based FPIC operation shows response that is in good agreement to that obtained from a simulation study conducted using MATLAB/Simulink.